Design of foundation rafts by uncoupled iterative method - Tornyos, Árpád; Czap, Zoltan (Computer Assisted Methods in Engineering and Science, 1999)
The authors developed a calculation module into a commercial finite element analysis (FEA) program, which is capable of calculating foundation rafts quickly, with correct results for the engineering practice. The calculation method is based on the so-called "uncoupled iterative method", wherein the structure and the soil continuum are analysed separately. The results of one analysis form the boundary conditions for the subsequent analysis as part of an iterative process. The connection between the raft and the soil is considered to be represented by the bedding modulus of the raft and by the soil stresses. The method provides the same displacements for the raft as for the soil surface, provided sufficient convergence can be reached if the raft is not elevated from the soil.